N‐Acylbenzotriazole as Efficient Ligand in Copper‐Catalyzed O‐Arylation Leading to Diverse Benzoxazoles. Issue 1 (9th January 2017) - Singh, Anoop S.; Singh, Mala; Mishra, Nidhi; Mishra, Snigdha; Agrahari, Anand K.; Tiwari, Vinod K.
Abstract: An establishment of (1 H ‐benzo[d][1, 2, 3]triazol‐1‐yl)(2‐methoxyphenyl)methanone as ligand was attained in intramolecular C ‐ O cross‐coupling of N ‐(2‐halophenyl)aryl/alkylamide derivatives to form 2‐Aryl/alkyl benzoxazole derivatives using CuI/K2 CO3 as catalytic system. A series of benzoxazoles was developed using this protocol and synthesized compounds were characterized using spectroscopic analysis (IR, MS, 1 H & 13 C NMR). Salient advantages associated with this pathway include easily available starting materials, cheap catalyst, highly stable ligand, wide substrate scope, smooth reaction, easy work‐up and high product yield. Abstract : An establishment of (1 H ‐benzo[d][1, 2, 3]triazol‐1‐yl)(2‐methoxyphenyl)methanone as ligand was attained in intramolecular C ‐ O cross‐coupling of N ‐(2‐halophenyl)aryl/alkylamide derivatives to form 2‐Aryl/alkyl benzoxazole derivatives using CuI/K2 CO3 as catalytic system. A series of benzoxazoles was developed using this protocol and synthesized compounds were characterized using spectroscopic analysis (IR, MS, 1 H & 13 C NMR).